1993
DOI: 10.3109/10401239309148922
|View full text |Cite
|
Sign up to set email alerts
|

Barbiturate Anticonvulsants in Refractory Affective Disorders

Abstract: Despite an increasing literature demonstrating both acute and long-term positive psychopharmacological effects of both valproate and carbamazepine, phenytoin has remained a controversial intervention, and barbiturate anticonvulsants have generally received poor press with regard to psychotropic effects. In the present investigation, 27 seizure-free, affectively ill patients who received therapeutic trials of primidone and/or mephobarbital after failing on antidepressants, lithium, carbamazepine, valproate, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…These include felbamate, gabapentin, lamotrigine, and vigabatrin. The older drugs phenytoin (Dreyfus 1981) and mysoline (Hayes 1993) have been reported as effective in some uncontrolled studies but their efficacy in bipolar illness remains largely unexplored on a systematic basis (see Table 7). …”
Section: Possible New Anticonvulsant Approaches To Mood Stabilizationmentioning
confidence: 98%
“…These include felbamate, gabapentin, lamotrigine, and vigabatrin. The older drugs phenytoin (Dreyfus 1981) and mysoline (Hayes 1993) have been reported as effective in some uncontrolled studies but their efficacy in bipolar illness remains largely unexplored on a systematic basis (see Table 7). …”
Section: Possible New Anticonvulsant Approaches To Mood Stabilizationmentioning
confidence: 98%
“…Another antiabsence mography (PET) or blood flow using 15 O PET. Preliminary data of Ketter et al [84] have indicated that those agent mysoline has been reported to be effective in some add-on studies by Hayes [91]. patients with baseline hypermetabolism are more likely to respond to carbamazepine, whereas those with hypometabolism are more likely to respond to the calcium Acetazolamide Acetazolamide is a carbonic anhydrase inhibitor channel blocker and putative anticonvulsant nimodipine.…”
Section: Ethosuximide and Mysolinementioning
confidence: 99%